The Effect of Problem-Based Learning on Mathematical Problem-Solving: A Meta-Analysis at the Junior Secondary Level - Veni Agustina; Mia Nurkanti (PT. Integrasi Sains Edukasi, 2025)
Mathematical problem-solving ability is a fundamental competency in secondary mathematics education; however, many students continue to face significant challenges in mastering this skill. In response, various instructional strategies have been implemented, among which Problem-Based Learning (PBL) has received considerable attention. This study aims to systematically and quantitatively examine the effect of PBL on junior high school students’ mathematical problem-solving abilities through a meta-analytic approach. A total of 24 empirical studies published between 2013 and 2024 were rigorously selected based on predefined inclusion criteria. The meta-analysis results indicate that PBL has a large and statistically significant impact on improving students’ problem-solving skills, with a mean effect size of 0.89, which falls within the high category. Furthermore, the effectiveness of PBL was found to vary across moderator variables, including implementation duration, assessment instrument type, and grade level. These findings suggest that PBL is an effective instructional strategy for enhancing students' critical thinking and problem-solving capabilities. The study recommends broader and more systematic implementation of PBL in schools, as well as targeted teacher training to support its optimal integration into classroom practice.